1994
DOI: 10.1557/jmr.1994.2976
|View full text |Cite
|
Sign up to set email alerts
|

Reactive ion etching of PbZr1−x TixO3 and RuO2 films by environmentally safe gases

Abstract: A new process for the reactive ion etching (RIE) of both PbZri-^T^Os (PZT) thin films and RuO2 electrodes is presented, employing etching gases with low ozone depletion potential (ODP) and global warming potential (GWP). The etching process has been investigated as a function of etching time, discharge power density, chamber pressure, and additive gas. Etch rates were in the range of 250-650 A/min and 100-400 A/min for PZT and RuO2, respectively. A large etch selectivity between PZT and RuO2 was optimized. Etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…It is very difficult to find a trade-off between a reasonable PZT etch rate, photoresist dimensional stability and removability. Other studies gives similar results in term of etching rates (10 to 40 nm/min) in HC 2 CIF 4 [32], in C 2 F 6 /Cl 2 [33] or in CF 4 /Cl 2 [34] gases recently, Chung et al [35] reported the etching process of PZT using ICP reactor and HBr/Ar gas mixture. An etch rate of 90 nm/min and a steep etch profile of 70 • has been achieved.…”
Section: Dry Etching Of Pzt Thin Filmssupporting
confidence: 54%
“…It is very difficult to find a trade-off between a reasonable PZT etch rate, photoresist dimensional stability and removability. Other studies gives similar results in term of etching rates (10 to 40 nm/min) in HC 2 CIF 4 [32], in C 2 F 6 /Cl 2 [33] or in CF 4 /Cl 2 [34] gases recently, Chung et al [35] reported the etching process of PZT using ICP reactor and HBr/Ar gas mixture. An etch rate of 90 nm/min and a steep etch profile of 70 • has been achieved.…”
Section: Dry Etching Of Pzt Thin Filmssupporting
confidence: 54%
“…CHClFCF 3 ͑DuPont trade name HCFC-124͒ was selected for this particular study, because it has been proven effective for complex metal oxides etching and is known to be less environmentally hazardous compared to the other hydrofluorocarbons. 14 In this letter, the preliminary experimental results on reactive etching of SrBi 2 Ta 2 O 9 and SrBi 2 Nb 2 O 9 are presented. The dependence of etch rates on chamber pressure and rf power are presented.…”
Section: ͓S0003-6951͑96͒01504-8͔mentioning
confidence: 99%
“…Patterning of PZT films has become an essential element of device fabrication. Several techniques have been developed for etching: wet chemical etching, 1 ion-beam etching ͑IBE͒, 2 reactive ion etching ͑RIE͒, [3][4][5] electron cyclotron resonance ͑ECR͒ etching, 6 and inductively coupled plasma ͑ICP͒ etching. 7 The RIE is widely used because it provides, in some etching conditions, high etch rate and selectivity, and also a high degree of anisotropy.…”
Section: Introductionmentioning
confidence: 99%